1+1>2: Learning from the interfacial modulation on single-atom electrocatalysts to design dual-atom electrocatalysts for dinitrogen reduction - Qiang Zhou; Feng Gong; Yunlong Xie; Rui Xiao (Green Energy & Environment, 2023)
Developing efficient electrocatalysts for converting dinitrogen to ammonia through electrocatalysis is of significance to the decentralized ammonia production. Here, through high-throughput density functional theory calculations, we demonstrated that the interfacial modulation of hexagonal boron nitride/graphene (hBN-graphene) could sufficiently improve the catalytic activity of the single transition metal atom catalysts for nitrogen reduction reaction (NRR). It was revealed that Re@hBN-graphene and Os@hBN-graphene possessed remarkable NRR catalytic activity with low limiting potentials of 0.29 V and 0.33 V, respectively. Furthermore, the mechanism of the enhanced catalytic activity was investigated based on various descriptors of the adsorption energies of intermediates, where the synergistic effect of hBN and graphene in the hybrid substrate was found to play a key role. Motivated by the synergistic effect of hybrid substrate in single-atom catalysts, a novel strategy was proposed to efficiently design dual-atom catalysts by integrating the merits of both metal components. The as-designed dual-atom catalyst Fe-Mo@hBN exhibited more excellent NRR catalytic performance with a limiting potential of 0.17 V, manifesting the solidity of the design strategy. Our findings open new avenues for the search of heterostructure substrates for single-atom catalysts and the efficient design of dual-atom catalysts for NRR.